2010
DOI: 10.1177/104063871002200132
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Orthopoxvirus-Associated Disease in Horses in Southern Brazil

Abstract: Abstract. An outbreak of severe cutaneous disease associated with an orthopoxvirus in horses in southern Brazil is described. Fourteen Crioulo mares and foals from a husbandry farm developed papules, and vesicles progressing to proliferative and exudative lesions on the muzzle, external nares, and external and internal lips. The vesicles eroded, and the proliferative lesions eventually bled and progressed to moist crusts and scars. The clinical signs lasted approximately 6-12 days, after which the animals prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 16 publications
0
19
2
Order By: Relevance
“…Furthermore, serological and epidemiological studies in Brazilian equine herds showed the presence of antibodies anti-OPV in animals from Midwest Brazil (BORGES et al, 2013;PERES et al, 2013). Recently, another VACV outbreak in horses was identified in Minas Gerais (MATOS et al, 2013), with clinical course similar to the VACV outbreak reported in Southern Brazil (BRUM et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Furthermore, serological and epidemiological studies in Brazilian equine herds showed the presence of antibodies anti-OPV in animals from Midwest Brazil (BORGES et al, 2013;PERES et al, 2013). Recently, another VACV outbreak in horses was identified in Minas Gerais (MATOS et al, 2013), with clinical course similar to the VACV outbreak reported in Southern Brazil (BRUM et al, 2010).…”
Section: Introductionmentioning
confidence: 88%
“…Although vesicular and exanthematic outbreaks occur frequently in dairy cattle in Brazil, VACV infection is rare in horses (KAMINJOLO Jr. et al, 1974;BRUM et al, 2010). Nonetheless, in 2008 a VACV outbreak, caused by two genetic and phenotypically divergent isolates was described in horses from Southern Brazil (BRUM et al, 2010;CAMPOS et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations